Pengaruh Price Discount dan Promo Gratis Ongkos Kirim terhadap Keputusan Pembelian pada Marketplace Shopee - Wulandari, Septia Putri; Jemadi, Jemadi (Jurnal Manajemen Strategis: Jurnal Mantra, 2025)
This research examines the influence of price discounts and free shipping promotions on purchasing decisions on Shopee, particularly among price-sensitive students. The sampling method used is accidental sampling with sample calculation using the Slovin formula, resulting in 100 respondents. Data analysis includes validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, F-tests, t-tests, determination coefficients, and data processing with SPSS 20. The research results show that price discounts and free shipping have a positive and significant effect on purchase decisions. Nevertheless, marketing strategies that focus on free shipping are more effective than simply offering price discounts in increasing customer purchase decisions.